Impact of managerial ownership on investment and liquidity constraints: Evidence from Chinese listed companies. - Vijayakumaran, R. (Elsevier., 2021)
We examine the impact of managerial ownership on investment and financial constraints in the context of China. Using the system generalized method of moments estimation of an investment Euler equation, we find that investment decisions are related to managerial ownership in two ways. First, managerial ownership exerts a positive direct effect on corporate investment decisions by aligning management’s incentives with the interests of shareholders. Second, managerial ownership helps to reduce the degree of financial constraints faced by firms, suggesting that managerial ownership acts as a form of credible guarantee to lenders, signaling the quality of investment projects to the capital markets. Our findings suggest that recent policies enacted by the Chinese government, aimed at reforming ownership structure and encouraging managerial ownership in listed firms, help reduce agency costs and asymmetric information; thereby facilitating firms’ investment efficiency. Our findings will be of interest to scholars, practitioners, and policy makers interested in the financial impacts of management-compensation contracts.
Keywords: Investment; Managerial ownership; Under-investment; Financial constraints; Ownership reform; State ownership